2013
DOI: 10.3109/08923973.2013.797993
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the relationship of paraoxonase-1 Q192R polymorphisms and the severity of lung disease in SM-exposed patients

Abstract: Late respiratory complications in patients suffering from pulmonary lesions due to sulfur mustard (SM) gas are asthma, chronic obstructive pulmonary disease and bronchiectasis. Recently PON1 antioxidant activity draws attention as the enzyme which prevents the oxidation of lipoproteins during oxidative stress. In this study we aimed to investigate PON1 192 polymorphisms and paraoxonase and arylesterase activity in the serum of SM-exposed lung disease patients. Also, we examined the detection of PON1 and apoA1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…PON1 is a serum enzyme primarily synthesized in the liver and secreted into the plasma where it associates with HDL. PON1 has multiple functions including the metabolism of pro-inflammatory, oxidized lipids in LDL and HDL, and has been implicated in the pathogenesis of several disorders including diabetes, coronary heart disease (CHD), cancer, and lung disease [ 5 , 27 ]. Our work in the K/BxN mouse model of RA recently showed that over-expression of the human PON1 transgene, which causes a twofold to threefold increase in circulating PON1 activity, reduces RA joint disease activity and associated with lower levels of the pro-inflammatory oxylipins 5-HETE and 15-HETE [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…PON1 is a serum enzyme primarily synthesized in the liver and secreted into the plasma where it associates with HDL. PON1 has multiple functions including the metabolism of pro-inflammatory, oxidized lipids in LDL and HDL, and has been implicated in the pathogenesis of several disorders including diabetes, coronary heart disease (CHD), cancer, and lung disease [ 5 , 27 ]. Our work in the K/BxN mouse model of RA recently showed that over-expression of the human PON1 transgene, which causes a twofold to threefold increase in circulating PON1 activity, reduces RA joint disease activity and associated with lower levels of the pro-inflammatory oxylipins 5-HETE and 15-HETE [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…The role of PON1 in lung disease remains largely unclear, although some studies have suggested a possible protective role in chronic obstructive lung disease, and inflammatory pulmonary disease related to mustard gas exposure [ 27 , 28 ]. The PON1 protein has been identified in non-ciliated bronchiolar epithelial cells (clara cells), which maintain the epithelium of the distal conducting airways of the lungs [ 29 ], and both the arylesterase activity and protein levels of PON1 have been identified in induced sputum from healthy volunteers [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Because the PON1 Q192R polymorphism is a major determinant of the enzyme activity of PON1, and has been associated with both vascular and pulmonary outcomes in the general population [12,26], we examined its association with disease outcomes in IIM patients. Clinical characteristics of IIM patients were first examined between PON1 QQ, QR and RR genotypes (Table 5).…”
Section: The Pon1 Q192r Polymorphism Associates With Iim Disease Char...mentioning
confidence: 99%